1994
DOI: 10.1063/1.868072
|View full text |Cite
|
Sign up to set email alerts
|

Laplace pressure driven drop spreading

Abstract: This work concerns the spreading of viscous droplets on a smooth rigid horizontal surface, under the condition of complete wetting (spreading parameter S > 0) with the Laplace pressure as the dominant force. Owing to the self-similar character foreseeable for this flow, a self-similar solution is built up by numerical integration from the center of symmetry to the front position to be determined, defined as the point where the free-surface slope becomes zero. Mass and energy conservation are invoked as the onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 17 publications
5
27
0
Order By: Relevance
“…The reason behind this phenomenon is that only relevant force is capillary pressure, which produces fairly small spreading velocities whose effects on the droplet spreading are visible only after 1 ms. Further time evolution shows that droplet shape does not change much between 0.25 s and 0.4 s, since the wall film thickness gradients on the edge of the droplet tend to zero. On the same picture could also be noticed that the behaviour of the droplet during the whole period of the simulation remains symmetrical, which is qualitatively in agreement with analytical results of Diez et al (1994). Quantitative comparison of simulation results and non-dimensional analytical droplet profile given in Figure 5 shows that the present numerical predictions are in good agreement with the analytical expression from Diez.…”
Section: Parabolic Dropletsupporting
confidence: 79%
See 2 more Smart Citations
“…The reason behind this phenomenon is that only relevant force is capillary pressure, which produces fairly small spreading velocities whose effects on the droplet spreading are visible only after 1 ms. Further time evolution shows that droplet shape does not change much between 0.25 s and 0.4 s, since the wall film thickness gradients on the edge of the droplet tend to zero. On the same picture could also be noticed that the behaviour of the droplet during the whole period of the simulation remains symmetrical, which is qualitatively in agreement with analytical results of Diez et al (1994). Quantitative comparison of simulation results and non-dimensional analytical droplet profile given in Figure 5 shows that the present numerical predictions are in good agreement with the analytical expression from Diez.…”
Section: Parabolic Dropletsupporting
confidence: 79%
“…The droplet is driven with Laplace (capillary) pressure as dominant force and other forces being absent or negligible. Similar tests were obtained by Diez et al (1994), who proposed analytical solution using lubrication theory, which neglects convective terms in momentum equation, and compared the proposed solution with experimental results. The problem can be observed as two dimensional because of axial symmetry.…”
Section: Test Casementioning
confidence: 53%
See 1 more Smart Citation
“…The droplet is driven with a Laplace (capillary) pressure as dominant force and other forces being absent or negligible. Similar tests were obtained by Diez et al (1994). He proposed an analytical solution using lubrication theory, which neglects convective terms in the momentum equation, and confirmed it experimentally.…”
Section: Validation Of Implemented Surface Tension Modelsupporting
confidence: 51%
“…The problem can be observed as a two-dimensional because of axial symmetry. Diez et al (1994) showed that the normalized film thickness h/h 0 can be expressed as a single function of the scaled radial position r/r f , irrespective of the time level.…”
Section: Validation Of Implemented Surface Tension Modelmentioning
confidence: 99%